Deportability and manifestations of suffering of immigrants and their families - Montes, Verónica (2019)
In this study, I examine the way in which deportation inflicts different  forms of suffering upon both immigrants themselves and their families.  Drawing on a series of open-ended interviews with Mexican immigrants  in the United States, as well as children of immigrants, and deportees, I examine not only the subjective condition of immigrants’ deportability status  but also how living in a constant state of fear affects every member of the  family. In each of the cases, I document the circumstances that contribute to the suffering of immigrants and their families. Finally, although all the  stories presented here were forged through pain and anxiety, ultimately,  these narratives demonstrate resistance and resilience within the migrant community.